Cobalt and nitrogen co-doped carbon nanotube, preparation method thereof and fuel cell
During the preparation of carbon nanotubes, using the induction of cobalt elements and hydrogen, heat treatment was carried out at high temperature to successfully synthesize co-doped carbon nanotubes, which solved the low synthesis efficiency of doped heteroatoms in the prior art. The problem of this is to achieve the efficient performance of fuel cell catalysts.
Patent Information
- Application Number
- CN202411717089.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art is difficult to efficiently and simply synthesize carbon nanotubes doped with heteroatoms, resulting in poor catalytic activity in fuel cells.
By performing the first heat treatment of the mixture in an oxygen environment of 500~600°C, a graphite phase carbon nitride precursor was obtained, and then a second heat treatment was performed under the induction of cobalt elements and hydrogen to obtain co-doping of cobalt and nitrogen. Heterocarbon nanotubes.
This method successfully synthesizes cobalt and nitrogen co-doped carbon nanotubes with better bicatalytic activity by pre-preparing the graphite phase carbon nitride precursor and cobalt element, which is suitable for fuel cell catalysts.
Smart Images

Figure CN119490178A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical materials, and in particular to cobalt-nitrogen co-doped carbon nanotubes, a preparation method thereof, and a fuel cell. Background Art
[0002] One-dimensional carbon nanotubes (CNTs) are considered to be ideal catalysts and high-quality conductive agents for fuel cells and secondary batteries due to their excellent conductivity, high degree of graphitization, excellent chemical stability, and ease of doping with heteroatoms or introducing metal sites for chemical modification. To date, there are four main techniques for the preparation of carbon nanotubes: arc discharge, laser ablation, molten salt embedding, and chemical vapor deposition, all of which require harsh conditions (arc, laser, high temperature ≥600°C) or additional templates / inducers. In addition, the doping of N atoms can be achieved by post-treating carbon nanotubes in a nitrogen atmosphere, but the nitrogen content is low. The most widely used but ineffective method is to synthesize carbon nanotube-based metal and nitrogen co-doped nanomaterials by attaching iron / cobalt macrocycles or polymer precursors to the surface of carbon nanotubes and then pyrolyzing them, because the modified active sites on carbon nanotubes often lead to their poor durability. Therefore, it is a major challenge to efficiently and simply synthesize carbon nanotubes doped with heteroatoms.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide cobalt and nitrogen co-doped carbon nanotubes and a preparation method thereof and a fuel cell, aiming to improve at least one of the problems mentioned in the background technology.
[0005] The present invention is achieved in that: In a first aspect, the present invention provides a method for preparing cobalt and nitrogen co-doped carbon nanotubes, comprising: The mixture is placed in an environment with oxygen at 500-600° C. for a first heat treatment for at least 1 hour to obtain a graphite phase carbon nitride precursor, wherein the mixture contains a cobalt salt and an amine compound uniformly dispersed with each other; Placing the graphite phase carbon nitride precursor in a reaction atmosphere, and performing a second heat treatment at a temperature of 495-950° C. for at least 1.5 h to obtain cobalt-nitrogen co-doped carbon nanotubes; The mass ratio of the amine compound to the cobalt salt calculated as cobalt element is 10000:6.20~248.0; The reaction atmosphere contains hydrogen, and the volume concentration of hydrogen is greater than or equal to 5%.
[0006] In an optional embodiment, the amine compound includes at least one of urea and dicyandiamide; Optionally, the amine compound is a mixture of urea and dicyandiamide; Optionally, the cobalt salt is cobalt chloride.
[0007] In an optional embodiment, the mass ratio of urea to dicyandiamide is 5-9:1-5; Preferably, the mass ratio of urea to dicyandiamide is 6.5-7.5:2.5-3.5.
[0008] In an optional embodiment, the mass ratio of the amine compound to the cobalt chloride is 10000:77-87.
[0009] In an optional embodiment, the method further includes obtaining a mixed material before the first heat treatment, and the method of obtaining the mixed material includes: Dispersing the amine compound and the cobalt source in deionized water, fully dissolving and mixing to obtain a mixed solution; Rapidly cooling the mixed solution to below -55°C at a cooling rate greater than 1°C / s to obtain a frozen material; The frozen material is freeze-dried to obtain a mixed material.
[0010] In an optional embodiment, the method of rapidly cooling the mixed solution to below -55°C at a cooling rate greater than 1°C / s to obtain the frozen material includes: placing the mixed solution in a liquid nitrogen environment to rapidly cool it to form the frozen material.
[0011] In an optional embodiment, ultrasonic stirring is used to fully dissolve and mix the amine compound and the cobalt source in deionized water to obtain a mixed solution.
[0012] In an optional embodiment, the heating rate of the first heat treatment is ≥1°C / min, preferably 4-6°C / min; Optionally, the first heat treatment time is 3 to 5 hours; Optionally, the heating rate of the second heat treatment is ≥1°C / min, preferably 8-12°C / min; Optionally, the second heat treatment time is 1.5 to 2.5 hours; Optionally, the reaction atmosphere is a mixed atmosphere of hydrogen and inert gas, wherein the volume concentration of hydrogen is 25-35%.
[0013] In a second aspect, the present invention provides a cobalt-nitrogen co-doped carbon nanotube, which is prepared by the preparation method of any one of the aforementioned embodiments.
[0014] In a third aspect, the present invention provides a fuel cell comprising the cobalt-nitrogen co-doped carbon nanotubes according to the aforementioned embodiment.
[0015] The present invention has the following beneficial effects: The preparation method provided by the present invention is to prepare a graphite phase carbon nitride precursor in advance, and then obtain cobalt and nitrogen co-doped carbon nanotubes through high-temperature heat treatment under the induction of cobalt element and hydrogen. The carbon nanotubes have better dual catalytic activity as fuel cell catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 The catalytic performance data of Examples 1 to 5 are shown in the figure on the left, which is a curve diagram showing the relationship between the potential and the current density of ORR, and the figure on the right is a curve diagram showing the relationship between the potential and the current density of OER; Figure 2 The catalytic performance data of Example 3, Examples 6-8 and Comparative Example 1, the left figure is a curve diagram of the relationship between the potential and the current density of ORR, and the right figure is a curve diagram of the relationship between the potential and the current density of OER; Figure 3 The catalytic performance data of the products obtained in Examples 7 to 11 and Comparative Examples 1 to 8 are shown in the figure on the left, which is a curve diagram showing the relationship between the potential and the current density of ORR, and the figure on the right is a curve diagram showing the relationship between the potential and the current density of OER; Figure 4 The cobalt-nitrogen co-doped carbon nanotubes (denoted as Co 50 / CNTs) microscopic morphology; Figure 5 The cobalt-nitrogen co-doped carbon nanotubes (denoted as Co 100 / CNTs) microscopic morphology; Figure 6 The cobalt-nitrogen co-doped carbon nanotubes (denoted as Co 150 / CNTs) microscopic morphology; Figure 7 The cobalt-nitrogen co-doped carbon nanotubes (denoted as Co 200 / CNTs) microscopic morphology; Figure 8 This is a microscopic morphology of cobalt and nitrogen co-doped carbon nanotubes prepared in Example 9; Fig. 9 This is a microscopic morphology of cobalt and nitrogen co-doped carbon nanotubes prepared in Example 10; Fig.10 This is a microscopic morphology of the cobalt and nitrogen co-doped carbon nanotubes prepared in Example 11; Fig.11 This is a microscopic morphology of the product obtained in Comparative Example 1; Fig.12 This is a microscopic morphology of the product obtained in Comparative Example 2; Fig.13 This is a microscopic morphology of the product obtained in Comparative Example 3; Fig.14 This is a microscopic morphology of the product obtained in Comparative Example 4; Fig.15 This is a microscopic morphology of the product obtained in Comparative Example 5; Fig.16 This is a microscopic morphology of the product obtained in Comparative Example 6; Fig.17 This is a microscopic morphology of the product obtained in Comparative Example 7. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0019] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0020] An embodiment of the present invention provides a method for preparing cobalt and nitrogen co-doped carbon nanotubes, comprising: The mixture is placed in an environment with oxygen at 500-600° C. for a first heat treatment for at least 1 hour to obtain a graphite phase carbon nitride precursor, wherein the mixture contains a cobalt salt and an amine compound uniformly dispersed with each other; Placing the graphite phase carbon nitride precursor in a reaction atmosphere, and performing a second heat treatment at a temperature of 495-950° C. for at least 1.5 h to obtain cobalt-nitrogen co-doped carbon nanotubes; The mass ratio of the amine compound to the cobalt salt in terms of cobalt element is 10000:6.20~248.0.
[0021] The reaction atmosphere contains hydrogen, and the volume concentration of hydrogen is greater than or equal to 5%.
[0022] The preparation method provided by the present invention is to prepare a graphite phase carbon nitride precursor in advance, and then obtain cobalt and nitrogen co-doped carbon nanotubes through high-temperature heat treatment under the induction of cobalt element and hydrogen. The carbon nanotubes have better dual catalytic activity as fuel cell catalysts.
[0023] The preparation method is specifically as follows: S1. Preparation of mixed materials The amine compound and the cobalt salt are mixed uniformly at the atomic level.
[0024] Specifically, the mixing method is: Ultrasonic stirring is used to fully dissolve and mix the amine compound and the cobalt source in deionized water to obtain a mixed solution; the mixed solution is rapidly cooled to below -55°C at a cooling rate greater than 1°C / s to obtain a frozen material; the frozen material is freeze-dried to obtain a mixed material.
[0025] The mass ratio of the amine compound to the cobalt salt in terms of cobalt element is 10000:6.20-248.0 (e.g., 10000:6.20, 10000:15, 10000:50, 10000:80, 10000:110, 10000:150, 10000:180, 10000:200, or 10000:248). The mass ratio may further be 10000:6.20-49.58 (e.g., 10000:6.20, 10000:12.40, 10000:24.79, 10000:37.185, or 10000:49.58), preferably 10000:12.40-49.58.
[0026] Optionally, the cobalt salt is, for example, cobalt nitrate, cobalt chloride, cobalt sulfate or the like.
[0027] Preferably, in order to further improve the catalytic activity of the obtained carbon nanotubes as a fuel cell catalyst, the mass ratio of the amine compound to cobalt chloride is 10000:77-87 (eg, 10000:77, 10000:82 or 10000:87).
[0028] Optionally, the amine compound includes at least one of urea and dicyandiamide. It should be noted that urea and dicyandiamide are only two options in the preferred embodiment of this case, which are mainly used to provide elements for preparing carbon nitride. Other types of amine compounds can be applied to this application as long as they can be used to prepare carbon nitride.
[0029] Preferably, in order to further improve the catalytic activity of the obtained carbon nanotubes as fuel cell catalysts, the amine compound is a mixture of urea and dicyandiamide.
[0030] Preferably, in order to further improve the catalytic activity of the obtained carbon nanotubes as a fuel cell catalyst, the mass ratio of urea to dicyandiamide is 5-9:1-5 (e.g., 5:5, 6:4, 7:3, 8:2 or 9:1), more preferably 6.5-7.5:2.5-3.5 (e.g., 6.5:3.5, 6:4, 7:3 or 7.5:2.5).
[0031] Optionally, the amount of deionized water used is based on the amount capable of completely dissolving the cobalt salt, urea and dicyandiamide.
[0032] In this step, the mixed solution is cooled quickly to form a frozen material in order to prevent the cobalt salt from crystallizing during the cooling process due to too slow cooling. Optionally, the rapid cooling method includes placing the mixed solution in a liquid nitrogen environment to rapidly cool it to form a frozen material.
[0033] It should be noted that, in some embodiments, the method for achieving uniform mixing of urea, dicyandiamide and cobalt salt at the atomic level can also be ball milling.
[0034] S2. First heat treatment The mixed material obtained in step S1 is placed in a muffle furnace, and heated to 500-600°C (e.g., 500°C, 550°C, or 600°C) at a heating rate of ≥1°C / min, preferably 4-6°C / min (e.g., 4°C / min, 5°C / min, or 6°C / min), and heat treated for at least 1 hour, preferably 3-5 hours (e.g., 3 hours, 4 hours, or 5 hours). CoO is obtained. x / g-C3N4.
[0035] In this step, amine compounds are used as raw materials, and the air entering the muffle furnace is thermally oxidized to form a layered structure and CoO with moderate hardness. x When the amine compound is a mixture of urea and dicyandiamide, the layered structure and hardness can be adjusted by adjusting the ratio of urea and dicyandiamide to obtain CoO with better performance. x / g-C3N4 precursor.
[0036] S3, Second heat treatment The CoO obtained in step S2 x / g-C3N4 is placed in a reaction atmosphere, and the reaction temperature is increased to 495-950°C (for example, 495°C, 550°C, 600°C, 700°C, 800°C, 900°C or 950°C), preferably to 495-550°C (for example, 495°C, 500°C, 510°C, 520°C, 540°C or 550°C) at a heating rate of ≥1°C / min, preferably 8-12°C / min (for example, 8°C / min, 10°C / min or ℃ / min), and heat treated for at least 1.5h, preferably 1.5-2.5h (for example, 1.5h, 2h, 2.5h) to obtain cobalt and nitrogen co-doped carbon nanotubes.
[0037] Optionally, the reaction atmosphere is a mixed atmosphere of hydrogen and an inert gas, wherein the volume concentration of hydrogen is preferably 25-35% (eg, 25%, 30% or 35%). Optionally, the inert gas is at least one of argon and nitrogen.
[0038] It should be noted that the reason for doping with cobalt is that only cobalt has been found to be a suitable metal for inducing graphite phase carbon nitride to form carbon nanotubes. Other transition metals (iron, nickel, manganese, zinc, copper) do not have the ability to induce graphite phase carbon nitride to form carbon nanotubes. Hydrogen concentration is one of the main conditions that determine the formation of carbon nanotubes. Only when the hydrogen concentration exceeds 5% can carbon nanotubes be effectively synthesized, and the higher the concentration, the easier it is to synthesize carbon nanotubes. The heat treatment temperature of this step needs to be guaranteed to be above 495°C. If it is lower than this temperature, graphite cannot be converted into carbon nanotubes.
[0039] The cobalt-nitrogen co-doped carbon nanotube provided in the embodiment of the present invention is prepared by the preparation method provided in the embodiment of the present invention and has excellent bifunctional catalytic activity as a fuel cell catalyst.
[0040] A battery provided by an embodiment of the present invention includes the cobalt-nitrogen co-doped carbon nanotubes provided by an embodiment of the present invention.
[0041] Example 1-Example 5 Ultrasonic stirring was used to fully dissolve urea, dicyandiamide and cobalt chloride hexahydrate in deionized water and mix them to obtain a mixed solution, wherein the total mass of urea and dicyandiamide was 10 g, the cobalt chloride hexahydrate was 100 mg, and the deionized water was 30 mL; The mixed solution is slowly poured into a rate beaker filled with clean liquid nitrogen to rapidly freeze the mixed solution into a frozen material, and then the frozen material is freeze-dried to obtain a mixed material.
[0042] The mixture was placed in a muffle furnace and heated to 550°C at 5°C / min and kept at this temperature for 4 h to obtain CoO x / g-C3N4; CoO x / g-C3N4 was transferred to a tube furnace, and a mixed atmosphere of argon and hydrogen was introduced into the tube furnace at a gas flow rate of 5 ppm, wherein the volume proportion of hydrogen was 30%. The temperature was raised to 500 °C at a rate of 10 °C / min and kept at this temperature for 2 h to obtain cobalt-nitrogen co-doped carbon nanotubes, denoted as Co 100 / CNTs.
[0043] The difference between Example 1 to Example 5 is only that the ratio of urea to dicyandiamide is different, as shown in Table 1.
[0044] Table 1 Mass ratio of urea and dicyandiamide in Example 1-Example 5
[0045] Example 6-Example 8 Ultrasonic stirring was used to fully dissolve urea, dicyandiamide and cobalt chloride hexahydrate in deionized water and mix them to obtain a mixed solution, wherein the total mass of urea and dicyandiamide was 10 g, the mass ratio of urea to dicyandiamide was 7:3, and the deionized water was 30 mL; The mixed solution is slowly poured into a rate beaker filled with clean liquid nitrogen to rapidly freeze the mixed solution into a frozen material, and then the frozen material is freeze-dried to obtain a mixed material.
[0046] The mixture was placed in a muffle furnace and heated to 550°C at 5°C / min and kept at this temperature for 4 h to obtain CoO x / g-C3N4; CoO x / g-C3N4 was transferred to a tubular furnace, and a mixed atmosphere of argon and hydrogen was introduced into the tubular furnace at a gas flow rate of 5 ppm, wherein the volume proportion of hydrogen was 30%. The temperature was raised to 500°C at a rate of 10°C / min and kept at that temperature for 2 h to obtain cobalt and nitrogen co-doped carbon nanotubes.
[0047] Example 6 to Example 8 are basically the same as Example 3, except that the amount of cobalt chloride hexahydrate used is different, as shown in Table 2.
[0048] Table 2 Amount of cobalt chloride hexahydrate used in Examples 6 to 8
[0049] Example 9 This embodiment is basically the same as Embodiment 7, except that the volume proportion of hydrogen in the mixed atmosphere introduced during the second heat treatment is set to 5%.
[0050] Example 10 This embodiment is basically the same as embodiment 7, except that the second heat treatment temperature is 495°C.
[0051] Embodiment 11 This embodiment is substantially the same as embodiment 7, except that the amount of cobalt chloride hexahydrate used is 25 mg.
[0052] Comparative Example 1 Ultrasonic stirring was used to fully dissolve urea and dicyandiamide in deionized water and mix them to obtain a mixed solution, wherein the total mass of urea and dicyandiamide was 10 g, the ratio between the two was 7:3, and the deionized water was 30 mL; The mixed solution is slowly poured into a rate beaker filled with clean liquid nitrogen to rapidly freeze the mixed solution into a frozen material, and then the frozen material is freeze-dried to obtain a mixed material.
[0053] The mixture was placed in a muffle furnace, heated to 550°C at 5°C / min, and kept at this temperature for 4 h to obtain g-C3N4; Transfer g-C3N4 to a tubular furnace, and introduce a mixed atmosphere of argon and hydrogen at a gas flow rate of 5 ppm, in which the volume proportion of hydrogen is 30%. The temperature is raised to 500°C at a heating rate of 10°C / min and kept warm for 2 h to obtain comparison sample 1, recorded as g-C3N4H2.
[0054] Comparative Example 2 This comparative example is substantially the same as Example 7, except that the cobalt chloride hexahydrate in Example 7 is replaced by an equal amount of nickel chloride hexahydrate. Comparative Sample 2 is obtained.
[0055] Comparative Example 3 This comparative example is substantially the same as Example 7, except that the cobalt chloride hexahydrate in Example 7 is replaced by an equal amount of ferric chloride hexahydrate. Comparative Sample 3 is obtained.
[0056] Comparative Example 4 This comparative example is substantially the same as Example 7, except that the cobalt chloride hexahydrate in Example 7 is replaced by an equal amount of copper chloride dihydrate. Comparative Sample 4 is obtained.
[0057] Comparative Example 5 This comparative example is substantially the same as Example 7, except that the cobalt chloride hexahydrate in Example 7 is replaced by an equal amount of manganese chloride tetrahydrate. Comparative Sample 5 is obtained.
[0058] Comparative Example 6 This comparative example is basically the same as Example 7, except that the volume proportion of hydrogen in the mixed atmosphere introduced during the second heat treatment is set to 4%.
[0059] Comparative Example 7 This embodiment is basically the same as Embodiment 7, except that the second heat treatment temperature is 490°C.
[0060] Comparative Example 8 This comparative example provides an existing method for preparing cobalt-nitrogen co-doped carbon nanotubes. The doping amounts of cobalt and nitrogen in the prepared carbon nanotubes are the same as those of the finished product prepared in Example 7.
[0061] The preparation method is specifically as follows: 200 mg of commercial multi-walled carbon nanotubes (CNT), 150 mg of Co(acac)2 and 1 g of dicyandiamide (DCD) were dispersed in 50 mL of deionized water, and then stirred and dispersed in a 50°C water bath for 8 h; the dispersed system was quickly frozen with liquid nitrogen and then freeze-dried in a freeze dryer to obtain the catalyst precursor CNT@DCD-Co; finally, CNT@DCD-Co was heated to an annealing temperature of 600°C at a heating rate of 2°C / min in a 10v% hydrogen / argon mixed atmosphere and annealed for 2 h.
[0062] Experimental example The cobalt and nitrogen co-doped carbon nanotubes prepared in each embodiment and comparative example were used as fuel cell catalysts to test the catalytic performance of ORR (oxygen reduction reaction) and OER (oxygen evolution reaction). The specific test method is: Electrode preparation: 2.5 mg of catalyst and 2.5 mg of conductive carbon black were added to 1000 µL of isopropanol solution and 10 µL of Nafion solution and ultrasonicated for 120 min to obtain a uniformly mixed ink solution. The obtained solution was evenly dropped on the polished electrode surface with a pipette and then dried in an oven at 35°C. The catalyst loading was controlled to be 0.2 mg cm -2 .
[0063] The four-electron oxidation (4e - For ORR) test, the rotating disk electrode speed was 1600 rpm.
[0064] The oxygen evolution reaction (OER) test was carried out in 1M KOH solution with a scan rate of 5mV / s and a scan range of 1.23V-1.8V (vs.RHE).
[0065] In the zinc-air assembly process, the air electrode was used as the cathode. 1 mg of the catalyst was dissolved in isopropanol and 5% Nafion solution and dropped on the carbon cloth. The loading area was ensured to be 1 mg / cm 2 , assembled on the battery cathode. A 0.3mm zinc sheet is used as the anode. The electrolyte is 6 mol / L KOH and 0.2 mol / L zinc acetate solution.
[0066] Figure 1The catalytic performance data of Examples 1 to 5 are shown in the figure on the left, and the relationship between the potential and current density of ORR is shown in the figure on the right, while the relationship between the potential and current density of OER is shown in the figure on the right. The ORR half-wave potential and the OER overpotential of each example are calculated, and the voltage difference ∆E is calculated. The voltage difference of Examples 1 to 5 is less than 0.714, indicating that Examples 1 to 5 all have excellent bifunctional catalytic activity, among which the cobalt and nitrogen co-doped carbon nanotubes prepared with a ratio of urea to dicyandiamide of 7:3 have the best catalytic activity.
[0067] Figure 2 The catalytic performance data of Example 3, Examples 6-8 and Comparative Example 1 are shown in the figure on the left. The relationship between the potential and the current density of ORR is shown in the figure on the right. The ORR half-wave potential and the OER overpotential of each Example and Comparative Example are calculated, and the voltage difference ∆E is calculated. The voltage difference of Examples 6 to 8 is less than 0.80, indicating that Examples 6 to 8 all have excellent bifunctional catalytic activity. Among them, the best is when the amount of cobalt chloride hexahydrate in Example 7 is 150 mg, Co 150 / CNTs have an excellent ORR half-wave potential of 0.871 V vs. RHE and a high OER of 1.521 V vs. RHE η=10mA / cm-2 The overpotential of the bifunctional catalytic voltage difference ∆E is as low as 0.65 V. The bifunctional catalytic voltage difference ∆E of Comparative Example 1 reaches 0.978 V, indicating that the preparation process of Comparative Example 1 is not doped with cobalt, and it is difficult to obtain a bifunctional catalyst with good catalytic performance. The main reason is that the carbon nitride in the graphite phase is not induced to transform into carbon nanotubes due to the absence of cobalt doping.
[0068] according to Figure 1-3 Statistical ORR half-wave potential and OER of Examples 7, 9 to 11 and Comparative Examples 1 to 8 η=10mA / cm-2 The overpotential is calculated and the voltage difference ∆E is recorded in Table 3.
[0069] Table 3 Data statistics of various embodiments and comparative examples
[0070] It can be seen from Table 1 that the cobalt-nitrogen co-doped carbon nanotubes prepared in various embodiments of the present invention have excellent bifunctional catalytic activity.
[0071] Comparing Examples 9, 10, and 11 with Example 7, the ∆E (1.173 V) of Example 9 is worse than that of Example 7, the ∆E (0.77 V) of Example 10 is worse than that of Example 7, and the ∆E performance of Example 11 is worse than that of Example 7. In addition, the SEM (e.g. Figure 8-10The results show that 5% hydrogen concentration, 495°C secondary heat treatment temperature, and 25 mg of cobalt chloride hexahydrate addition can all produce carbon nanotubes in good condition, but the poor catalytic performance of Examples 9-11 shows that 5% hydrogen, 495°C temperature, and 25 mg of cobalt chloride hexahydrate are the lower limits for synthesizing carbon nanotubes. Comparing Comparative Example 1 with Example 7, the performance of Comparative Example 1 is worse than that of Example 7, which indicates that it is difficult to obtain a bifunctional catalyst with better catalytic performance if cobalt is not doped during the preparation of carbon nanotubes. Comparing Comparative Examples 2-5 with Example 7, the performance of Comparative Examples 2-5 is worse than that of Example 7, which indicates that it is difficult to obtain the carbon nanotubes with good performance of the present invention if other transition metal elements such as nickel, iron, copper, and manganese are doped; Comparing Comparative Example 6 with Example 7, the performance of Comparative Example 6 is worse than that of Example 7, which indicates that if the proportion of hydrogen in the preparation process is too low, it is difficult to prepare cobalt and nitrogen co-doped carbon nanotubes with good performance; Comparing Comparative Example 7 with Example 7, the performance of Comparative Example 7 is worse than that of Example 7, which indicates that if the heat treatment temperature is too low during the preparation process, it is difficult to obtain cobalt and nitrogen co-doped carbon nanotubes with good performance; Comparative Example 8 provides a method for directly doping nitrogen and cobalt in finished carbon nanotubes. Comparing Comparative Example 8 with Example 7, the performance of Comparative Example 5 is worse than that of Example 7, which indicates that the product prepared by the preparation method of the present invention of doping nitrogen and cobalt before the carbon nanotubes are generated has better bifunctional catalytic activity. Although the bifunctional catalytic voltage difference ∆E of Comparative Example 8 is smaller than that of other embodiments of the present invention, it can be foreseen that if the cobalt and nitrogen co-doped carbon nanotubes with the same doping amount as the various embodiments of the present invention are prepared according to the direct doping method provided in Comparative Example 8, their performance is obviously worse than that of the various embodiments of the present invention.
[0072] Experimental Example 2 The microscopic morphology of the products obtained in Example 3, Example 6 to Example 8, and Comparative Examples 1 to Comparative Examples 4 are shown respectively as follows: Figures 4 to 11 shown.
[0073] Figure 4 The cobalt-nitrogen co-doped carbon nanotubes (denoted as Co 50 / CNTs) SEM (left) and TEM (right); Figure 5 The cobalt-nitrogen co-doped carbon nanotubes (denoted as Co 100 / CNTs) SEM (left) and TEM (right); Figure 6 The cobalt-nitrogen co-doped carbon nanotubes (denoted as Co 150 / CNTs) SEM (left) and TEM (right); Figure 7The cobalt-nitrogen co-doped carbon nanotubes (denoted as Co 200 / CNTs) SEM (left) and TEM (right). Figures 4 to 7 It can be seen that the fibrous carbon nanotubes are stacked together, which indicates that the cobalt- and nitrogen-coated carbon nanotubes are produced in each embodiment.
[0074] Figure 8 The SEM image of the product obtained in Example 9, with the left and right sides showing the morphology at different magnifications. Figure 8 It can be seen that in Example 9, cobalt-nitrogen co-doped carbon nanotubes can still be produced at a minimum hydrogen concentration of 5%.
[0075] Fig. 9 The SEM image of the product obtained in Example 10, with the left and right sides showing the morphology at different magnifications. Fig. 9 It can be seen that in Example 10, cobalt and nitrogen co-doped carbon nanotubes can still be produced at the lowest secondary heat treatment temperature of 495°C.
[0076] Fig.10 The SEM image of the product obtained in Example 11, with the left and right sides showing the morphology at different magnifications. Fig.10 It can be seen that in Example 11, cobalt-nitrogen co-doped carbon nanotubes can still be prepared at a minimum addition amount of 25 mg of cobalt chloride hexahydrate.
[0077] Fig.11 The TEM image of the product obtained in Comparative Example 1, with the left and right sides showing the morphology at different magnifications. Fig.11 It can be seen that the product prepared in Comparative Example 1 does not have a carbon nanotube structure, which means that carbon nanotubes cannot be prepared if cobalt is not doped during the preparation process; Fig.12 The TEM image of the product obtained in Comparative Example 2, with the left and right sides showing the morphology at different magnifications. Fig.12 It can be seen that the product obtained in Comparative Example 2 does not have a carbon nanotube structure, which means that carbon nanotubes cannot be obtained if nickel is doped instead of cobalt during the preparation process. Fig.13 The TEM image of the product obtained in Comparative Example 3, with the left and right sides showing the morphology at different magnifications. Fig.13 It can be seen that the product obtained in Comparative Example 3 does not have a carbon nanotube structure, which means that carbon nanotubes cannot be obtained if cobalt is not doped but iron is doped instead during the preparation process. Fig.14 The TEM image of the product obtained in Comparative Example 4, with the left and right sides showing the morphology at different magnifications. Fig.14It can be seen that the product obtained in Comparative Example 4 does not have a carbon nanotube structure, which means that carbon nanotubes cannot be obtained if copper is doped instead of cobalt during the preparation process. Fig.15 The TEM image of the product obtained in Comparative Example 5, with the left and right sides showing the morphology at different magnifications. Fig.15 It can be seen that the product obtained in Comparative Example 5 does not have a carbon nanotube structure, which means that carbon nanotubes cannot be obtained if manganese is doped instead of cobalt during the preparation process. Fig.16 The TEM image of the product obtained in Comparative Example 6, with the left and right sides showing the morphology at different magnifications. Fig.16 It can be seen that the product obtained in Comparative Example 6 does not have a carbon nanotube structure, which means that carbon nanotubes cannot be obtained if the proportion of hydrogen in the preparation process is too low; Fig.17 The TEM image of the product obtained in Comparative Example 7, with the left and right sides showing the morphology at different magnifications. Fig.17 It can be seen that the product obtained in Comparative Example 7 does not have a carbon nanotube structure, which means that carbon nanotubes cannot be obtained if the heat treatment temperature is too low during the preparation process.
[0078] Therefore, if you want to completely convert graphite phase carbon nitride into carbon nanotubes, you need to ensure cobalt doping, a sufficient amount of hydrogen and a suitable heat treatment temperature to achieve this.
[0079] In summary, the preparation method provided in the embodiment of the present invention is to prepare a graphite phase carbon nitride precursor in advance, and then obtain cobalt and nitrogen co-doped carbon nanotubes through high-temperature heat treatment under the induction of cobalt element and hydrogen. The carbon nanotubes have better dual catalytic activity as fuel cell catalysts.
[0080] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing cobalt and nitrogen co-doped carbon nanotubes, characterized in that: include: The mixture is placed in an environment with oxygen at 500-600° C. for a first heat treatment for at least 1 hour to obtain a graphite phase carbon nitride precursor, wherein the mixture contains a cobalt salt and an amine compound uniformly dispersed with each other; Placing the graphite phase carbon nitride precursor in a reaction atmosphere, and performing a second heat treatment at a temperature of 495-950° C. for at least 1.5 h to obtain cobalt-nitrogen co-doped carbon nanotubes; The mass ratio of the amine compound to the cobalt salt in terms of cobalt element is 10000:6.20-248.0; The reaction atmosphere contains hydrogen, and the volume concentration of hydrogen is greater than or equal to 5%.
2. The preparation method according to claim 1, characterized in that: The amine compound includes at least one of urea and dicyandiamide; Optionally, the amine compound is a mixture of urea and dicyandiamide; Optionally, the cobalt salt is cobalt chloride.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the urea to the dicyandiamide is 5-9:1-5; Preferably, the mass ratio of the urea to the dicyandiamide is 6.5-7.5:2.5-3.
5.
4. The preparation method according to claim 2, characterized in that: The mass ratio of the amine compound to the cobalt chloride is 10000:77-87.
5. The preparation method according to claim 1, characterized in that: Before the first heat treatment, the mixed material is obtained. The method of obtaining the mixed material includes: Dispersing the amine compound and the cobalt source in deionized water, fully dissolving and mixing to obtain a mixed solution; Rapidly cooling the mixed solution to below -55°C at a cooling rate greater than 1°C / s to obtain a frozen material; The frozen material is freeze-dried to obtain the mixed material.
6. The preparation method according to claim 5, characterized in that: The method of rapidly cooling the mixed solution to below -55°C at a cooling rate greater than 1°C / s to obtain the frozen material includes: placing the mixed solution in a liquid nitrogen environment to rapidly cool it to form the frozen material.
7. The preparation method according to claim 5, characterized in that: Ultrasonic stirring is used to fully dissolve the amine compound and the cobalt source in the deionized water and mix them to obtain a mixed solution.
8. The preparation method according to claim 1, characterized in that: The heating rate of the first heat treatment is ≥1°C / min, preferably 4-6°C / min; Optionally, the first heat treatment time is 3 to 5 hours; Optionally, the heating rate of the second heat treatment is ≥1°C / min, preferably 8-12°C / min; Optionally, the second heat treatment time is 1.5 to 2.5 hours; Optionally, the reaction atmosphere is a mixed atmosphere of hydrogen and inert gas, wherein the volume concentration of hydrogen is 25-35%.
9. A cobalt-nitrogen co-doped carbon nanotube, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. A fuel cell, characterized in that: It comprises the cobalt and nitrogen co-doped carbon nanotubes as claimed in claim 9.